2002
DOI: 10.1002/app.11404
|View full text |Cite
|
Sign up to set email alerts
|

Studies on morphology and mechanical properties of PP/HIPS blends from postconsumer plastic waste

Abstract: ABSTRACT:The aim of this work was to study the compatibilizing effect of the triblock copolymer poly(styrene-bethylene-co-butylene-b-styrene) (SEBS) on the morphology and mechanical properties of virgin and recycled polypropylene/high-impact polystyrene (PP/HIPS) blends. The components of the blend were obtained from municipal plastics waste (MPW), with the PP obtained from blue mineral water bottles, symbolized as PP b , and the HIPS from disposable cups. These materials were preground, washed only with water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 9 publications
2
18
0
4
Order By: Relevance
“…Table 3 summarizes the main results from the TSE runs of WEEEBR, TBV and TBR under different processing conditions. Both E and σy tend to be slightly higher in the recycled materials than in the virgin materials, as has also been observed previously for HIPS, PP and compatibilised blends of these two [30]. No significant differences were found in the elongation at yield (εy), except perhaps for TBV processed at 60 rpm and T1 that was the most ductile material, and exhibited a In the TSE reprocessing of WEEEBR, the screw rotation rate and barrel temperature were varied independently in order to study their influence on the mechanical properties of the collected and reprocessed blend.…”
Section: Mechanical Propertiessupporting
confidence: 85%
“…Table 3 summarizes the main results from the TSE runs of WEEEBR, TBV and TBR under different processing conditions. Both E and σy tend to be slightly higher in the recycled materials than in the virgin materials, as has also been observed previously for HIPS, PP and compatibilised blends of these two [30]. No significant differences were found in the elongation at yield (εy), except perhaps for TBV processed at 60 rpm and T1 that was the most ductile material, and exhibited a In the TSE reprocessing of WEEEBR, the screw rotation rate and barrel temperature were varied independently in order to study their influence on the mechanical properties of the collected and reprocessed blend.…”
Section: Mechanical Propertiessupporting
confidence: 85%
“…Considerando uma pesquisa mais ampla sobre filmes especiais obtidos com plásticos de resíduo urbano desenvolvida por este Grupo, blendas de poliolefinas e HIPS pós-consumo foram estudadas quanto ao efeito da adição de agentes compatibilizantes sobre as propriedades das blendas e dos filmes obtidos com as mesmas [2,[17][18][19] . No presente trabalho, foram realizados estudos comparativos do efeito da adição de copolímeros multibloco SBS e linear SEBS, especificamente em blendas de HDPE e HIPS pós-consumo.…”
Section: Resultsunclassified
“…O procedimento para a recuperação mecânica da matéria prima foi o convencional descrito em publicações anteriores do grupo [2,18,19] . Os agentes compatibilizantes comerciais SEBS Kraton® G e SBS Styrolux® 684D, são da Kraton e da Basf, respectivamente.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…The morphological, viscosity, and interfacial tension results showed that SEBS is a better compatibilizer for PP/PS blends than SBS. Santana and Campomanes 15,16 studied the compatibilizing effect of SEBS on the morphology and mechanical properties of virgin and recycled PP/HIPS blends. SEBS reduced the diameter of dispersed HIPS particles and improved the adhesion between the dispersed phase and the matrix.…”
Section: Introductionmentioning
confidence: 99%